The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.36076/ppj.2017.e424
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Ligamentum Flavum Area as a Morphological Parameter of Lumbar Central Spinal Stenosis

Abstract: Background: Hypertrophy of the ligamentum flavum (LF) has been considered as a major cause of lumbar central spinal stenosis (LCSS). Previous studies have found that ligamentum flavum thickness (LFT) is correlated with aging, disc degeneration, and lumbar spinal stenosis. However, hypertrophy is different from thickness. Thus, to evaluate hypertrophy of the whole LF, we devised a new morphological parameter, called the ligamentum flavum area (LFA). Objectives: We hypothesized that the LFA is a key morphologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…LDH in elderly patients are often complicated by canal stenosis resulting from the hypertrophy of the facet joints and ligamentum flavum. [19][20][21] Under such circumstances, these pathologies may be the main culprit responsible for sciatica or claudication and thus, discectomy alone may not be promising in relieving neurological symptoms. Instead of discectomy, decompression of the narrowed spinal canal should be the focus of the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…LDH in elderly patients are often complicated by canal stenosis resulting from the hypertrophy of the facet joints and ligamentum flavum. [19][20][21] Under such circumstances, these pathologies may be the main culprit responsible for sciatica or claudication and thus, discectomy alone may not be promising in relieving neurological symptoms. Instead of discectomy, decompression of the narrowed spinal canal should be the focus of the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the reason for thickening, studies have identified the epiligament in the ligamentum flavum, comprising collagenous fibers, while enlargement of the epiligament led to more collagenous than natural elastic fibers and canal tapering. Furthermore, the ligamentum flavum area has been compared with more sensitive measurement parameters than the ligament flavum thickness, playing a more valuable role (17). Close to the ventral wall of the canal, the herniation of intervertebral disc would narrow the spinal canal.…”
Section: Discussionmentioning
confidence: 99%
“…13 Regarding the mechanism of the dynamic component of LSS, several articles have reported that posture-induced or axial pressure-induced elastic deformation of LF was the main contributor. [14][15][16][17][18][19][20][21] Lumbar extension or standing position may cause two adjacent laminas to move closer, followed by LF thickening and infolding. By contrast, lumbar flexion or lying flat position may cause the two-adjacent lamina to separate, resulting in the stretching and thinning of LF as well as the disappearance of LF infolding.…”
Section: Dynamic Components Of Lssmentioning
confidence: 99%